2019
DOI: 10.3390/c5020025
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Graphene-Reinforced Nanocomposites with Improved Fracture Toughness in Net Shape for Complex 3D Structures via Digital Light Processing

Abstract: A solvent-free method to fabricate graphene-reinforced nanocomposites in net shape via digital light processing (DLP) 3D printing has been developed in this work. The effect of graphene nanofillers on resin viscosity and wettability for various printing parameters has been examined, with a systematic characterization of the mechanical and thermomechanical properties. With the addition of 0.5 wt.% graphene nanoplatelets in the resin, the flexural modulus and fracture toughness have been improved by 14% and 28% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Han et al [ 183 ] used SLM technology to prepare titanium/hydroxyapatite (Ti/HA) with quasi‐continuous ratios, in which the ratio of HA varied from 0 to 5 wt% in each functional gradient, providing a wide range of nanohardness (5.11–8.36 GPa) and fracture toughness (3.41–0.88 MPa m 1/2 ), which could be tailored to match those of cortical and cancellous bones. Kawai et al [ 184 ] designed and 3D printed a functionally graded scaffold made of polycaprolactone (PCL) and β‐tricalcium phosphate with spatially controlled porosity, degradation and mechanical strength to reconstruct necrotic bone tissue in the femoral head. It was shown that a combination of FGS scaffolds and bone marrow‐derived mononuclear cells can improve the core decompression outcome in the early stage of osteonecrosis of the femoral head by providing both enhanced biological and biomechanical cues in the osteonecrotic area.…”
Section: Multifunctional Properties and Applicationsmentioning
confidence: 99%
“…Han et al [ 183 ] used SLM technology to prepare titanium/hydroxyapatite (Ti/HA) with quasi‐continuous ratios, in which the ratio of HA varied from 0 to 5 wt% in each functional gradient, providing a wide range of nanohardness (5.11–8.36 GPa) and fracture toughness (3.41–0.88 MPa m 1/2 ), which could be tailored to match those of cortical and cancellous bones. Kawai et al [ 184 ] designed and 3D printed a functionally graded scaffold made of polycaprolactone (PCL) and β‐tricalcium phosphate with spatially controlled porosity, degradation and mechanical strength to reconstruct necrotic bone tissue in the femoral head. It was shown that a combination of FGS scaffolds and bone marrow‐derived mononuclear cells can improve the core decompression outcome in the early stage of osteonecrosis of the femoral head by providing both enhanced biological and biomechanical cues in the osteonecrotic area.…”
Section: Multifunctional Properties and Applicationsmentioning
confidence: 99%
“…Conversely, DIW, SLA and DLP use liquid raw materials. Ultrasonication is the most common method to achieve the optimal dispersion of nanomaterials in liquid-based raw materials [ 236 , 238 , 239 , 240 ], although other mechanical mixing methods have also been used [ 229 ]. Sometimes, when the viscosity is high, a solvent is added, which promotes dispersion of the nanomaterial [ 237 ].…”
Section: Additive Manufacturing Of Bone Tissue-engineered Scaffoldmentioning
confidence: 99%
“…G increased the tensile and flexural properties of the matrix. Feng et al [ 240 ] also fabricated DLP samples comprising the same PU resin and 0.5 wt.% GNPs. In this case, the flexural modulus was improved by 14%, while fracture toughness increased by 28%.…”
Section: 3d Printed Scaffolds With Carbon-based Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to conventional processing methods, AM methods may offer GPMCs better mechanical property enhancements as the layer-by-layer fabrication method can align the nanoplatelets. Feng et al [177] fabricated 0.5 wt.% graphene reinforced PU resin using a DLP method. In this case, the flexural modulus and fracture toughness were improved by 14 % and 28 %, respectively, compared to the neat resin.…”
Section: Mechanical Properties and Strain Sensor Applicationmentioning
confidence: 99%